PENGARUH TIME BUDGET PRESSURE, DUE PROFESSIONAL CARE DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT DENGAN PERILAKU DISFUNGSIONAL AUDITOR SEBAGAI MODERATOR (Study Empiris Pada Kantor Akuntan Publik Di Pekanbaru Dan Medan) - Marisa Fitria; Emrinaldi Nur DP; Devi Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study was conducted to see whether the time budget pressure, due professionalis care and ethics of auditors effect on audit quality and auditor dysfunctional behavior as a moderator, either directly or indirectly. The population in this study were all auditors working in Public Accounting Firm (KAP) and is listed on the Directory Indonesian Institute of Certified Public Accountants (IAPI) in 2011 in the city of Pekanbaru and Medan.The data used are primary data obtained through the questionnaire respondents (sample) studies that specifically collected by researchers to answer the research questions. Data analysis methods used for testing the hypothesis is multiple regression (multiple regression).The results showed that 1) Time budget pressure direct impact on audit quality. 2) Time budget pressure indirect effect, through moderation dysfunctional behavior auditors on audit quality. 3) Due professional care directly affects the quality of the audit. 4) Due professional care indirect effect through the moderation of dysfunctional behavior auditors on audit quality. 5) Ethics auditor has no direct influence on the quality of the audit. 6) Ethical no effect indirectly through the dysfunctional behavior of auditors to audit quality. 7) The coefficient of determination is 0.682 which shows the influence of independent variables used in the model study on audit quality as the dependent variable was 68.2% while the rest (31.8%) is explained by other variables not included in this research model.Keywords: Quality, Dysfunctional,Budget and Professional